Pão ou aço ou aço e pão? industrialização e segurança alimentar no Brasil: o dilema de Josué de Castro - Silva, Reginaldo De Lima e (2023)
This work aims to bring the issue of hunger in the view of Josué de Castro to the academic discussion. However, it is a critical work that seeks to highlight the historical and geoeconomic differences of the problem. Time and the work “Geography of Hunger” written in 1946 take center stage in the work, since the economic diagnoses brought by Castro are questioned here, since the historical period in which Castro elaborates his work cannot be equated to the days Therefore, the most advanced scientific base for the time falls short of what humanity has managed to achieve in the 21st century. Therefore, it is important to highlight that the issue of hunger in the times of Josué de Castro took on different characteristics than today. Brazil's capacity to produce food was, at that time, insufficient to guarantee food supply to meet the needs of Brazilians. Today, Brazil lives a different reality. Food production is breaking records and therefore hunger must have different causes. The Marxist methodology is used in this work, seeking to highlight contradictions and the reality of each historical period, mainly during the period of greatest industrial development, which was the period between the years 1930 and 1980. In this way, through the demonstration of a Brazil that was heading for full industrial development, we seek to dialogue with Josué de Castro, bringing different thoughts to this dialogue, with emphasis on Ignácio Rangel who, with his original form and his transformative profile and clearly in the field of Marxism, is capable of bringing to light an economic diagnosis that could contribute to the criticism of Josué de Castro. Finally, we intend to bring out the relationships between hunger and industrialization, demonstrating that the hunger dilemma presented by Castro (steel or bread) can be answered today, at a historical moment in which Brazil experienced its industrial development.